Формування якості білих столових виноградних виноматеріалів, вироблених в умовах ДП «Первомайский винзавод» АР Крим - Гапріндашвілі, Нона Арчилівна; Гаприндашвили, Нона Арчиловна; Gaprindashvili, Nona; Войцехівський, В. І.; Войцеховский, В. И.; Voytsekhivskyy, V.; Воронова, С. С.; Voronova, S.; Воронова, С. С. (My University, 2012)
En: Established the factors affecting the quality of a white table grape wine made subsidiary company "Pervomaysky winery» of AR Crimea.
Formation of quality a white table grape wine produced in se "pervomayske winery" of AR Crimea
Keywords: strawberry; sort; chemical composition; wine; quality; сорт; якість; виноматеріал; хімічний склад